Febrile Proteinuria in Hospitalized Children: Characterization of Urinary Proteins - Evgenia Gurevich; Evgenia Gurevich; Eytan Israel; Eytan Israel; Yael Segev; Daniel Landau; Daniel Landau (Frontiers Media S.A., 2018)
Background: Transient proteinuria during febrile illness is a common phenomenon. Recent studies have re-examined the pathophysiology of proteinuria and new urinary markers to characterize it, including B7-1 (CD80), which is expressed also in glomerular podocytes and influences the glomerular barrier.Aim: To investigate the pattern of proteinuria in febrile non-renal diseases, including B7-1.Methods: We prospectively analyzed urine samples of 44 febrile children and 28 afebrile controls for different protein components: albumin (glomerular marker), β2-microglobulin (tubular marker), uromodulin (Tamm Horsfall protein-THP, a renal endogenous protein) and B7-1. Febrile illness was characterized as focal bacterial vs. viral. Exclusion criteria were underlying renal disease, steroid treatment or urinary tract infection.Results: Elevated urine albumin (64.5 ± 10.3 vs. 17.8 ± 4 mg/g, mean ± S.E.M., p = 0.0009) and β2-microglobulin (1.44 ± 0.34 vs. 0.182 ± 0.03 mg/g, mean ± S.E.M., p = 0.005] and decreased uromodulin (10.5 ± 1 vs. 26.7 ± 2.2 Arbitrary units, mean ± S.E.M., p = 0.0001) excretion were found during febrile illness vs. controls. Urine B7-1 was also increased in the febrile group (0.27 ± 0.05 vs. 0.07 ± 0.01 ng/ml, mean ± S.E.M., p = 0.001), and was the only marker which was significantly higher in bacterial vs. viral disease.Conclusions: Febrile proteinuria is not generalized: while proteins of both glomerular and tubular origin increase, uromodulin decreases. Urine B7-1 is increased during fever, more significantly in bacterial infections. Thus, urinary B7-1 may be used as an additional marker to differentiate between febrile states of bacterial vs. viral origin.